The Implementation of Quantum Teaching Learning Model to Improve Learning Outcomes of Class V Students SD Borong Jambu II of Makassar - Sabillah, Bellona Mardhatillah; Sukmawati, Sukmawati (Universitas Malikussaleh, 2020)
This study aims to improve social studies learning outcomes in grade V at SD Borong Jambu II Makassar by implementing the quantum teaching-learning model. This research is a Classroom Action Research (PTK), which is divided into two cycles with four stages, namely: planning, acting, observing, and reflecting repeatedly. The subjects of this study were students of grade V at SD Borong Jambu II Makassar, totaling 30 students. The instruments used to obtain data in this study consisted of tests, observation sheets, and questionnaires. This data analysis technique was carried out by analyzing learning outcome data, analyzing data from interviews, and analyzing field note data. The pre-action results were 33.33% who got a value of ≥75, then after learning using the quantum teaching model increased to 60% in cycle I increased to 30 students or all students earned a score of ≥75 in cycle II. It can be concluded that learning using the quantum teaching model by doing variations shows that the criteria for success in the study are fulfilled. This can be seen from the increase in grade V students in social studies score at SD Borong Jambu II of Makassar.